Industrial policy in East Asia: Lessons for Europe - Ha-Joon Chang (EIB Papers, 2006)
This paper critically examines the role of industrial policy in the economic development of East Asian countries with a view to drawing lessons for other countries, especially European ones. It describes the evolution of industrial policies in Japan, Korea, Taiwan, and Singapore and evaluates the East Asian industrial policy experience - in general and in relation to the East Asian miracle, the 1997 financial crisis, and the Japanese stagnation since the 1990s. In drawing lessons for other countries, the paper discusses the transferability of the 'East Asian model' - or any other economic model - to other countries and highlights the determinants of industrial policy successes and failures. A key conclusion is that there is scope for successful industrial policy even in countries that have reached the technological frontier and want to push it further.
Keywords: 330; Industriepolitik; Wirkungsanalyse; Ostasien; EU-Staaten